Curcumin, EGCG and apigenin in cervical cancer: mechanistic insights and therapeutic potential - Asiri, Abdulaziz; Bokahri, Bayan T.; Sadaf,; Eisa, Alaa Abdulaziz; Aljohani, Hashim M.; Nofal, Wesam; Kausar, Tahreem; Najm, Mohammad Zeeshan (Frontiers in Pharmacology, 2025)
Cervical cancer (CC) continues to be the major cause of death from cancer in women worldwide and highlights the necessity for novel therapeutic approaches that target key oncogenic pathways. Conventional treatments, including chemotherapy and radiotherapy, exhibit significant limitations, including drug resistance, toxicity, and limited durability of response, highlighting the need for improved strategies. In recent years, Phytochemicals like curcumin, EGCG, and apigenin have demonstrated potent anticancer effects by modulating multiple dysregulated pathways in CC. These natural compounds exhibit multi-targeted effects, influencing signaling cascades such as PI3K/Akt, JAK/STAT, Wnt/β-catenin, and NF-κB, which drive tumor progression and metastasis. While plant-derived compounds like curcumin, EGCG, and apigenin have shown promising anticancer effects in preclinical models, there is a critical lack of comprehensive reviews that integrate mechanistic insights, clinical progress, and bioavailability challenges. Specifically, gaps remain in correlating these compounds’ modulation of cervical cancer-relevant signaling pathways with clinical outcomes, as well as in synthesizing recent innovations in nanotechnology that enhance their pharmacokinetics. A comparative evaluation highlights their mechanistic overlaps in regulating oncogenic signaling and their potential for synergistic combinations with conventional therapies to enhance treatment efficacy and overcome drug resistance. While bioavailability and systemic stability hinder clinical translation, advancements in nanotechnology and targeted delivery systems offer promising solutions. Future research should prioritize optimizing formulations and conducting large-scale clinical studies to facilitate the integration of plant bioactives into CC therapy, ultimately improving patient outcomes. Despite increasing interest in phytochemicals for cervical cancer treatment, current literature lacks comprehensive synthesis of studies addressing their molecular mechanisms, clinical efficacy, and novel strategies such as nanotechnology to enhance bioavailability.